The factors that contribute to the performance of procurement staff in Holcim Malaysia Sdn. Bhd. / Mohd Fahmy Mohd Abdul Rahman and Nur Fatimah Razali - Mohd Abdul Rahman, Mohd Fahmy; Razali, Nur Fatimah (Faculty of Business and Management, 2014)
The purchasing profession has been gaining recognition in developed countries faster than in developing countries and to compare with other profession, the procurement profession has received only limited attention in developing countries (Matechack, 2009). In many developing countries, many companies have not managed to advance the purchasing profession either because of lack of manager to recognize the procurement profession or because top management does not support and fully understand the requirement competencies for effective development of the purchasing and supply chain function (Msimangira, 2003). Nowadays, the profession of procurement staff is getting good response from public in developing countries. This is due to procurement function has been increasingly gaining importance as a crucial role within organizations. Most of the companies are very particular in choosing their procurement staff because procurement staff is important in increasing company profitability and reducing cost. Every decision that taken by departments has involved procurement staff that can gave impact on overall cost when a decisions is made. Furthermore, in Holcim Malaysia, procurement is view as one of the strategic function in department logistic and imports. The existence of procurement section is to improve and increase the company profitability. It can be achieve through procurement function and their responsibility, for instance by helping to reduce material prices and cost, and also help in identifying better supplier that can give good quality of goods with best price. In this research, the researcher wants to study which are the factors that contribute to the performance of procurement staff in Holcim Malaysia. The procurement staff will be evaluated by all Holcim workers that 3